Comparison of Environmental Scanning Electron Microscopy in Low Vacuum or wet mode for the investigation of cell biomaterial interactions - Mattarozzi, Monica; Manfredi, Edoardo; Lorenzi, Andrea; Smerieri, Arianna; Di Blasio, Alberto; Macaluso, Guido; Lumetti, Simone; Galli, Carlo (Acta Biomedica Atenei Parmensis, 2016)
Aim: The aim of the present study was to investigate the efficacy of environmental scanning electron microscopy (ESEM), in low vacuum mode (LV-ESEM) and in wet mode (wet-ESEM) in the assessment of cell-material interactions. Methods: Mouse calvaria MC3T3 cells (ATCC) were seeded on commercially pure machined titanium discs of 10 mm diameter in Dulbecco modified MEM, 10% Fetal Bovine Serum, 1% Penicillin and Streptomycin and 1% Glutamine. Samples were then processed for microscope observation by rinse in Phosphate Buffer saline and fixation in 4.5% Glutaraldehyde. Samples were then rinsed in Sodium Cacodylate buffer and observed or dehydrated in alcohol prior to LV-ESEM observation. Fresh samples in 0.9% NaCl solution were observed in wet- ESEM. Results: No significant loss of detail was observed when dehydrated or non dehydrated samples were analysed at LV-ESEM.The observation of fresh samples in wet-ESEM however proved difficult for the need to eliminate water which forms a layer covering the sample, thus hiding cell surface details. When reducing the vapor pressure in the chamber, the layer evaporated and NaCl immediately started to precipitate and cells collapsed, thus no further investigation was possible. Conclusions: The use of low vacuum-ESEM after cell fixation, but without dehydration or gold sputter coating proved a viable alternative to traditional high vacuum SEM observation.